High‐Performance Capacitive Deionization and Killing Microorganism in Surface‐Water by ZIF‐9 Derived Carbon Composites. Issue 12 (20th October 2021) - Cao, Shuai; Chen, Tingting; Zheng, Shasha; Bai, Yang; Pang, Huan
Abstract: The protection and regeneration of the water environment is currently one of the most critical concerns for the sustainable development of human society. To solve the water crisis, the use of capacitive deionization (CDI) technology to extract fresh‐water that is suitable for human consumption from abundant surface‐water is a feasible solution. In this work, a cobalt benzimidazole frameworks (ZIF‐9) derived carbon composites with a unique quasi‐microcubic morphology is synthesized and used the as‐prepared materials as an electrode material for the CDI. Interestingly, the ZIF‐9 derived carbon composites exhibit an impressive desalination capacity of 55.4 mg g –1 and can be reused. Measurements in surface‐water (Beijing‐Hangzhou Grand Canal, Slender West Lake, Initial rainwater, Rain water) show that this CDI technology based on ZIF‐9 derived carbon composites not only has a strong adsorption effect on metal ions but also can remarkably kill microorganisms. The results show that the technology can effectively kill bacteria ( Escherichia coli and Bacillus ) and algae with 95% and 91.7% inhibition rates, respectively. This work provides a valuable example for the use of metal–organic framework‐derived carbon composites as high‐performance electrode materials of CDI and opens a new direction for promoting the application of CDI in surface‐water. Abstract : The obtained ZIF‐9 derived carbon composite exhibits excellent desalination ability due to its specific micro/nanostructure and composition. In addition, it is also found that the capacitive deionization system can effectively kill microorganism in surface‐water (Beijing‐Hangzhou Grand Canal, Slender West Lake, Initial rainwater, Rain water), resulting in a more drinkable freshwater.